Volatile Constituents and Cytotoxic Activity of Khaya grandifoliola and Khaya senegalensis Flower Extracts. Issue 2 (2nd April 2016) - El Souda, Sahar S.; Aboutabl, Elsayed A.; Maamoun, Amal A.; Hashem, Fatma A.
ABSTRACT: The volatiles obtained from fresh flowers of Khaya grandifoliola C.DC. and Khaya senegalensis A.Juss. by hydro-distillation method were analyzed by gas chromatography and gas chromatography–mass spectrometry. Sesquiterpenes represent 86.32% and 80.86% of the identified volatile compounds of K. grandifoliola (KgO) and K. senegalensis (KsO) oil, respectively. Caryophyllene-oxide (23.01%), isocaryophyllene (Z) (21.99%), and α -humulene (13.46%) were the main compounds identified in KgO, whereas in KsO they were caryophyllene oxide (14.85%), β -caryophyllene (43.59%), and α -humulene (15.72%). The volatiles were tested for cytotoxic activity against liver (HepG-2), breast (MCF-7), and colon (HCT-116) human cancer cell lines . K. grandifoliola and K. senegalensis oils displayed cytotoxic activity with IC50 (21.6, 26.1, and 37.6 μ g.mL) and (61.1, 79.7, and 61 μ g.mL), respectively. Sesquiterpene content of Khaya oils may contribute to their cytotoxic activity .